Fractal Geometry‐Based Decrease in Trimethoprim‐Sulfamethoxazole Concentrations in Overweight and Obese People. (21st November 2016) - Hall, RG; Pasipanodya, JG; Meek, C; Leff, RD; Swancutt, M; Gumbo, T
Abstract : Trimethoprim‐sulfamethoxazole (TMP‐SMX) is one of the most widely drugs on earth. The World Health Organization recommends it as an essential basic drug for all healthcare systems. Dosing is inconsistently based on weight, assuming linear relationships. Given that obesity is now a global "pandemic" it is vital that we evaluate the effect of obesity on trimethoprim‐sulfamethoxazole concentrations. We conducted a prospective clinical experiment based on optimized design strategies and artificial intelligence algorithms and found that weight and body mass index (BMI) had a profound effect on drug clearance and volume of distribution, and followed nonlinear fractal geometry‐based relationships. The findings were confirmed by demonstrating decreased TMP‐SMX peak and area under the concentration‐time curves in overweight patients based on standard regression statistics. The nonlinear relationships can now be used to identify new TMP‐SMX doses in overweight and obese patients for each of the infections caused by the >60 pathogens for which the drug is indicated.